Laws and practices on local governance in Vietnam - Trang, Tang Thi Thu; Linh, Nguyen Thi Ngoc; Dai, Nguyen Van; Hoan, Ha Trong (International Journal of Innovative Research and Scientific Studies, 2025)
Local governance is a form of governance and administration carried out by local government agencies to realize the goal of state management in the territory. However, there are certain differences: Local governance emphasizes the interaction between the government and the people in the management and administration of social activities; local government management emphasizes the legal regulations and administrative measures of government agencies. This study addresses local governance in terms of legal regulations and the practice of people’s participation in local governance in the context of Vietnam’s political and social characteristics: The government mobilizes people’s participation; people participate in local governance both directly and indirectly. Based on the theoretical framework, the author conducted a survey of 250 people and 250 leaders of commune-level government agencies in three localities representing three regions of Vietnam, including Son La province (North), Quang Ngai province (Central), and Tra Vinh province (South). The survey results show that people are mobilized to participate in local governance, but mainly in an indirect form. From the results of this study, the author discusses the issue of research on innovation and improvement of laws so that people can directly participate more in the activities of government agencies, contributing to improving the effectiveness of local governance in Vietnam.